Does the glaze application on Y-TZP surface improve the bond strength to pressed veneering ceramic? - Rodrigues, Vinícius Anéas [UNESP]; Paradella, Thaís Cachuté [UNESP]; Coelho, Arianne Valim Pinto [UNESP]; Souza, Karina Barbosa; Bottino, Marco Antonio [UNESP]; de Melo, Renata Marques [UNESP]; Özcan, Mutlu; Souza, Rodrigo Othávio Assunção e (Taylor & Francis, 2020)
The objective of this study was to verify the influence of glaze application on the shear bond strength between Y-TZP and veneering ceramic. Thirty square-shaped blocks (12.5 × 15 × 1.5 mm) of sintered zirconia (Vita In Ceram YZ for inLab, VITA Zahnfabrik) were prepared, randomly divided into three groups (n = 10), according to the factor ‘glaze application’ (c–control/ g–powder and liquid/ gs–spray). On each zirconia surface, a cylinder of PM9 (Vita) ceramic was built (∅: 3 mm; height: 3 mm), according to the experimental group. Specimens were thermocycled (12,000 cycles/5 °C/55 °C ± 2 °C) and submitted to shear testing in a universal testing machine (1 mm/min). Analysis of fractured specimens ware performed through stereomicroscopy and SEM. Data were statistically analyzed through one-way ANOVA, Tukey’s test (5%) and Weibull's analysis. ANOVA revealed that the factor ‘glaze application’ (p = 0.001) was significant. The mean (±SD) shear bond data (MPa) were PM9c–41.52 (±11.82); PM9g–24.14 (±12.82); PM9gs–21.06 (±14.48). There were no significant differences among glazed types for bond strength and Weibull modulus (p > 0.05), however the Characteristic strength (σ o) decreased significantly after the application of the glaze, regardless of the group. The predominant type of failure was adhesive (76.66%) followed by mixed (23.34%). It can be concluded that, within the limitations of this study, the glazing application on Y-TZP surface, either powder and liquid or spray, did not improve the bond strength to pressed veneering ceramic.
Keywords: bond strength; ceramics; glazing; Zirconia